STEM Concept in Islamic Communication Development: A Conceptual Paper - Nur Choiro Siregar; Dewi Anggrayni; Warsito; Aris Gumilar (KOMUNIKA, 2025)
The integration of STEM (Science, Technology, Engineering, and Mathematics) concepts across various academic fields has attracted significant scholarly attention, particularly regarding its application in the realm of Islamic communication. This conceptual paper explores the potential of STEM as a framework for advancing communication strategies within Islamic contexts. It begins by defining Islamic communication, which involves the dissemination of Islamic values and teachings through diverse communication mediums. The paper then investigates how the interdisciplinary nature of STEM emphasizing problem-solving, innovation, and technology can enhance and refine communication practices within the Islamic world. Drawing from existing literature in both Islamic studies and STEM education, this paper examines how STEM principles can provide novel perspectives for improving the effectiveness of Islamic messaging, addressing contemporary challenges in media, and fostering digital literacy among Muslim communities. Furthermore, the paper explores the role of STEM in the development of innovative communication tools and platforms that align with Islamic ethical values while engaging effectively with modern audiences. Through a conceptual framework, this research aims to propose pathways for integrating STEM into Islamic communication practices, suggesting strategies to expand the reach and impact of Islamic messages in a rapidly evolving digital landscape. The paper concludes by identifying potential directions for future research, particularly in exploring the practical applications of STEM in Islamic communication, and its implications for Islamic scholars and communication professionals.